IMPLEMENTASI HAK TRADISI DALAM UNDANG-UNDANG TENTANG DESA PADA TRADISI MAYSARAKAT DESA DI KECAMATAN LELEA KABUPATEN INDRAMAYU - Gunardi Gunardi; Rasji Rasji (PROSIDING SERINA, 2021)
The Law on Villages regulates and recognizes the traditional rights of village communities as living rights, which can be implemented and maintained by village communities. These traditional rights need to be implemented in government and village community life. One of the village communities who have many traditional rights is the village community in Lelea District, Indramayu Regency. How is the implementation of traditional village rights in the Law on Villages in rural communities in Lelea District, Indramayu Regency? The problems mentioned above have been investigated through normative legal research methods and empirical legal research. The results of the study illustrate that the Indramayu Regency Government has implemented traditional village rights into Regional Regulation Number 4 of 2017 concerning Village Government. Furthermore, these traditional rights are implemented in the practice of village community life, for example in the village community of Lelea District, Indramaayu Regency. The form of implementation is that local, sub-district and village governments allow village communities to carry out their traditional rights, for example the celebration of Ngarot culture, Alms of the Earth, Alms of visiting, celebration of Mapag Sri, and others. The results of the research are very useful for the development of rural legal science and rural communities in implementing and maintaining their traditional rights.